(untitled) (UNIZIK Journal of STM Education, 2026)
This study examined the comparative effects of 4MAT and 5E instructional approaches on the academic achievement and critical thinking disposition of biology students in Imo State, Nigeria. For this study, a quasi-experimental design was used. The sample comprised 85 SS2 Biology students, selected using purposive sampling technique. Using two validated instruments named Biology Achievement Test (BAT) and Biology Critical Thinking Disposition Rating Scale (BCTDRS), data on student achievement and critical thinking disposition were collected. To test the instruments for reliability, Kuder Richardson 20 was used for the BAT and Cronbach Alpha statistics for the BCTDRS and coefficients of 0.77 and 0.75 were obtained respectively. To answer the questions posed, the researcher utilized mean and standard deviation scores, while the hypotheses were tested with ANCOVA F-test at 0.05 significance. The findings of the study are as follows: students taught Biology by employing the 5E instructional approach significantly outperformed those taught using the 4MAT method (p<.05), while those taught using the 4MAT method significantly performed better in their critical thinking disposition than their counterparts taught using the 5E (p<.05). The researcher recommended that biology teachers adopt the 5E method for improved academic achievement and 4MAT for improved critical thinking disposition.